A Numerical Model to Simulate the Motion of a Lifesaving Module During its Launching from the Ship’S Stern Ramp - Dymarski Paweł; Dymarski Czesław (Polish Maritime Research)
The article presents a numerical model of object motion in six degrees of freedom (DoF) which is intended to be used to simulate 3D motion of a lifesaving module during its launching from a ship using a stern ramp in rough sea. The model, of relatively high complexity, takes into account both the motion of the ship on water in changing sea conditions, and the relative motion of the ramp with respect to the ship.